The Fundamental Analysis of the CANSLIM Method in the Non-Cyclical Consumption Sector during the Covid-19 Period on the Indonesia Stock Exchange (IDX) on the Indonesian Sharia Stock Index (ISSI) - Dadan Ramdhan; Ismalia, Hani (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study uses secondary data by analyzing the stocks available in the Indonesian Sharia Stock Index (ISSI) in the capital market using the CANSLIM method. The CANSLIM method is a method of fundamental and momentum analysis used over a long period. This method fundamental analyzes with three criteria which include (1) Quarterly EPS, (2) Annual EPS, (3) New product, management, and high. Of the 21 issuers in the Indonesian Sharia Stocks Index (ISSI), there are only 14 issuers that meet the criteria for research problems. Companies with stock codes ADES, ROTI, and SKLT have almost perfect fundamental anaylsis of the CANSLIM method criteria, namely 3/3. The CANSLIM method affects stock returns because it uses fundamental analysis and momentum analysis, such as the current condition of Covid-19, and this method can be used over a long period. So this research is helpful for investors who can scan stocks with the potential for the long term, CANSLIM method can be used as an alternative method in choosing stocks to invest in, and also to help the decision to buy and sell shares.